An Epidermoid cyst of the upper lip in a completely edentulous geriatric female: A rare case with clinicoradiological report - Raman, Praveena; Raghuram, P H (Indian Journal of Case Reports, 2020)
Epidermal cysts are intradermal or subcutaneous (non-odontogenic), developmental pathologies occurring in the head and neck region with an incidence ranging from 1.6% to 6.9%. They represent